2008
DOI: 10.1007/s00464-008-9778-2
|View full text |Cite
|
Sign up to set email alerts
|

CO2 pneumoperitoneum increases systemic but not local tumor spread after intraperitoneal murine neuroblastoma spillage in mice

Abstract: CO(2) pneumoperitoneum increased intrahepatic metastasis, but not local peritoneal carcinosis in a murine neuroblastoma model. This suggests that laparoscopy could promote systemic dissemination of intraperitoneally spilled tumor cells when no chemotherapy is applied. It remains to be determined whether this is due to local immune suppression or direct modulation of tumor cell behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 48 publications
2
15
0
1
Order By: Relevance
“…In case of neuroblastoma, the most frequent solid childhood tumor, data are inconsistent. While series with small, localized and well-encapsulated tumors showed a good feasibility of laparoscopic resection [6], higher rates of metastases were found after minimally invasive neuroblastoma resection in experimental settings [4,5].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In case of neuroblastoma, the most frequent solid childhood tumor, data are inconsistent. While series with small, localized and well-encapsulated tumors showed a good feasibility of laparoscopic resection [6], higher rates of metastases were found after minimally invasive neuroblastoma resection in experimental settings [4,5].…”
Section: Discussionmentioning
confidence: 97%
“…Many cases have been reported in which different types of malignant tumors have metastasized after laparoscopy [1][2][3][4][5]. The pneumoperitoneum, usually with CO 2 , is a crucial feature of laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reports concluded that laparoscopic resection was acceptable in terms of feasibility and safety. Although one case of port-site metastasis after biopsy of a posttransplant Burkitt lymphoma in a child was recently reported [16], there have been no reports about port-site metastasis after abdominal minimally invasive resection procedures for pediatric malignancies [17]. No reports have provided long-term oncologic results or large-scale comparative studies with conventional operation cases.…”
Section: Discussionmentioning
confidence: 99%
“…This especially concerns the use of carbon dioxide (35, 36). However, after being used for a relevant time with respective follow-up, clinical experiences with laparoscopy for pediatric abdominal malignancies seem to indicate that there are no relevant differences in outcome compared to open surgical procedures.…”
Section: Abdominal Tumorsmentioning
confidence: 99%